PERILAKU BULLYING TERHADAP PESERTA DIDIK KELAS VIII SMP MUHAMMADIYAH 1 PONTIANAK TAHUN 2018 - Kurniawan, Danni Candra; Astuti, Indri; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractViolent acts of bullying experienced by children is the treatment that will impact the long term and would be a nightmare that never disappear from the memories of children who become victims. Based on information from teacher observation and BK, directly at the Junior High School Muhammadiyah 1 Pontianak that learners who seem doing the bullying. Therefore, researchers feel interested to conduct research on Junior High School Muhammadiyah 1 Pontianak because researchers want to find out more about bullying behavior in the students of Junior High School Muhammadiyah 1 Pontianak.The problem in this research is